Explanatory Research Knowledge Sharing and Knowledge heterogeneity on Higher Education Business performance through Learning Value Sharing: Explanatory Riset Knowledge Sharing dan Knowledge heterogeneity terhadap kinerja Bisnis Perguruan Tinggi melalui Sharing Value Pembelajaran - Sumartik Sumartik; Muhammad Yani; Galuh Ratmana Hanum; Dhea Ariesta Putri; Nur Laili Maulidiyah (Academia Open, 2023)
This study investigates the optimization of Knowledge Heterogeneity among practitioners in higher education through the dissemination of diverse expertise via the Practitioner-Led Teaching Program. The research, conducted within the context of the Kampus Merdeka initiative, employs a quantitative approach grounded in the positivist paradigm, complemented by structured interviews with practitioners to bolster questionnaire item indicators. Data was collected using saturated sampling from a population of 30 educators spanning 29 programs at a university. Employing SEM PLS analysis, the findings underscore that the sharing of knowledge and practitioner expertise significantly heightens academic performance, as manifested by an 87% enhancement in shared value across learning activities. This research underscores the pivotal role of practitioner engagement in enriching educational quality and aligning curricula with industry demands, thereby fostering valuable implications for educational institutions worldwide. Highlights: Optimizing Knowledge Diversity: Investigating the impact of diverse practitioner expertise on higher education outcomes. Practitioner-Led Engagement: Emphasizing the role of practitioners in enriching academic quality and relevance. Enhanced Academic Performance: Demonstrating an 87% increase in shared value through knowledge exchange, contributing to improved learning activities and educational outcomes. Keywords: Knowledge Heterogeneity, Practitioner-Led Teaching, Value Sharing, Higher Education, Academic Performance.